Disruption mitigation with high-pressure helium gas injection on EAST tokamak. (12th January 2018) - Chen, D.L.; Shen, B.; Granetz, R.S.; Qian, J.P.; Zhuang, H.D.; Zeng, L.; Duan, Y.; Shi, T.; Wang, H.; Sun, Y.; Xiao, B.J.
Abstract: High pressure noble gas injection is a promising technique to mitigate the effect of disruptions in tokamaks. In this paper, results of mitigation experiments with low-Z massive gas injection (helium) on the EAST tokamak are reported. A fast valve has been developed and successfully implemented on EAST, with valve response time  ⩽150 μ s, capable of injecting up to 7 × 10 22 particles, corresponding to 300 times the plasma inventory. Different amounts of helium gas were injected into stable plasmas in the preliminary experiments. It is seen that a small amount of helium gas ( N H e ≃ N p l a s m a ) can not terminate a discharge, but can trigger MHD activity. Injection of 40 times the plasma inventory impurity ( N H e ≃ 40 × N p l a s m a ) can effectively radiate away part of the thermal energy and make the electron density increase rapidly. The mitigation result is that the current quench time and vertical displacement can both be reduced significantly, without resulting in significantly higher loop voltage. This also reduces the risk of runaway electron generation. As the amount of injected impurity gas increases, the gas penetration time decreases slowly and asymptotes to (̃7 ms). In addition, the impurity gas jet has also been injected into VDEs, which are more challenging to mitigate that stable plasmas.